The Role of Visual, Auditory, and Kinesthetic Learning Styles in Optimizing Arabic Language Learning - Nur Azizah; Adelia Irsyadillah Al Hidjaz; Alma Idatun Nahlah; Abd-elsalam Elhewy, Rewan Khalil (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
Learning style is one of the supporting factors for students in obtaining learning material. However, each individual has a different learning style, including visual, auditory and kinesthetic. Therefore, a teacher is required to be active and innovative in creating learning, so that students can maximize learning in their own way. To answer the problem formulation of what are the characteristics of visual, auditory and kinesthetic learning styles in Arabic language learning? The research uses qualitative methods with a literature study approach to theoretically examine the characteristics of visual, auditory and kinesthetic learning styles in Arabic language learning. Based on studies conducted by researchers, it was found that the visual learning style tends to be used for learning Arabic through the media of images, videos and writing. Meanwhile, the auditory learning style supports listening and speaking skills through methods such as discussions, lectures or listening to audio. Meanwhile, the kinesthetic learning style provides benefits in movement-based learning activities, practice and direct experience, such as role playing. By understanding this learning style, a teacher can develop more adaptive learning to improve Arabic language learning.